PENGARUH RASIO PROFITABILITAS TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR (SEKTOR ANEKA INDUSTRI) YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2020 (JAPB, 2022)
This study aims to determine the effect of profitability ratios on financial distress in manufacturing companies (multiple industrial sectors) listed on the Indonesian stock exchange in 2019-2020. The approach used in this research is a quantitative descriptive approach. The research sample is a manufacturing company in the various industrial sectors listed on the Indonesia Stock Exchange which has distributed financial reports for the 2019-2020 period that meet the criteria, namely 33 companies per year, so for a total sample of 66 observations. In this study, the technique used is a quantitative approach in which the information or data contained in this study is presented in the form of numbers. Based on the research results, it was found that there was an effect of the profitability ratio on financial distress in manufacturing companies (various industrial sectors) listed on the Indonesia Stock Exchange in 2019-2020 as seen from the results of one-sided testing using a significance level of α = 5% (0, 05) so that the results show significant. And t count = 5.572 > t table = 2.040. Based on the results of data analysis through the SPSS program, it shows that there is an effect of the profitability ratio on financial distress in manufacturing companies (various industrial sectors) listed on the Indonesia Stock Exchange in 2019-2020 of 56% and the remaining 44% is influenced by other factors outside of this study. Keywords: Profitability Ratios, Financial Distress, SPSS.